Repeated-root bidimensional (μ, ν)-constacyclic codes of length 4pt.2r. (13th October 2020) - Patel, Shikha; Prakash, Om
Let p be an odd prime. The main concern of this article is to study all the repeated-root bidimensional ( μ, ν )-constacyclic codes of length 4 p t .2 r over the finite field 𝔽 p m . Here, we provide all the self-dual repeated-root bidimensional (1, 1)-constacyclic and (−1, 1)-constacyclic codes of length 4 p t .2 r over 𝔽 p m . We also discuss the repeated-root bidimensional ( η, 1)-constacyclic codes of length 4 p t .2 r over 𝔽 p m . Moreover, it has been shown that these structures are useful in the construction of linear complementary dual ( LCD ) codes and self-dual codes. As an example, we are listed all the repeated-root bidimensional ( μ, ν )-constacyclic codes of length 72 over the finite field 𝔽27 .